Motu proprio papieża Franciszka Mitis Iudex Dominus Iesus. Prezentacja dokumentu - Góralski, Wojciech (Ius Matrimoniale, 2015)
Francis’ Motu Proprio Mitis Iudex, published on September 8, 2015, which is devoted to the reform of canons of the of the Code of Canon Law related to laws on marriage annulment, along with the attached Instruction, constitutes an important novum in relation to current law. In order to meet the expectations of spouses who got divorced and remarried (civil marriage), the new document makes a far reaching reform of the marriage process, which becomes shortened and simplified. The author presents the provisions of Motu proprio and Instruction, at the same time indicating important tasks which the Conferences of Bishops, diocesan bishops and court Christians have to face. The most important innovations of the new document are: removing the requirement of two instances, enabling the possibility of a single court and introducing processus brevior before bishop. It appreciates the care of the highest Church legislator of the faithful who require special need in ascertaining the truth about the marriage which de facto ceased to exist.